2020
DOI: 10.1080/14767058.2020.1844659
|View full text |Cite
|
Sign up to set email alerts
|

A single-center experience on exchange transfusion therapy in 123 full-term cases of severe neonatal hyperbilirubinemia in Wuhan

Abstract: Objective: To describe the clinical experience in application of exchange transfusion therapy (ETT) in the treatment of severe neonatal hyperbilirubinemia. Methods: The clinical data and examination results of severe neonatal hyperbilirubinemia fullterm cases treated by ETT were analyzed retrospectively, the etiology and risk factors of severe neonatal hyperbilirubinemia were statistically analyzed, and the statistical characteristics of the children in each etiological group and the incidence of adverse event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
4
2
Order By: Relevance
“…Pediatricians should consider the possibility of hTTP in neonates when they have thrombocytopenia after birth in the absence of severe infection, asphyxia, or intrauterine growth restriction. Thrombocytopenia is one of the common complications of exchange transfusion, with incidence ranging from 38% to 64% 25,26 . But in this study, thrombocytopenia was present in all newborns with hTTP before exchange transfusion, and the platelet count gradually returned to normal after the exchange transfusion.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Pediatricians should consider the possibility of hTTP in neonates when they have thrombocytopenia after birth in the absence of severe infection, asphyxia, or intrauterine growth restriction. Thrombocytopenia is one of the common complications of exchange transfusion, with incidence ranging from 38% to 64% 25,26 . But in this study, thrombocytopenia was present in all newborns with hTTP before exchange transfusion, and the platelet count gradually returned to normal after the exchange transfusion.…”
Section: Discussioncontrasting
confidence: 51%
“…Thrombocytopenia is one of the common complications of exchange transfusion, with incidence ranging from 38% to 64%. 25,26 But in this study, thrombocytopenia was present in all newborns with hTTP before exchange transfusion, and the platelet count gradually returned to normal after the exchange transfusion. Therefore, considering the timing of thrombocytopenia around exchange transfusion is important in neonates with severe jaundice.…”
Section: Discussioncontrasting
confidence: 49%
“…We know that ET can improve the outcomes of neonates with severe hyperbilirubinemia, and once the ET indication is reached, ET should be administered as early as possible. However, the safety of ET is still a concern, 29 especially for preterm infants, and a retrospective cohort study found that infants with GA 29 weeks were more likely to die during ET than term infants. 16 In the current study including three provincial centers, we found that most of the ET-related adverse events were laboratory abnormalities that were asymptomatic and treatable, such as thrombocytopenia and hypocalcemia, and this was consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of ET has declined remarkably, the incidence of ET-related morbidity and mortality has not followed suit [ 38 ]. Table 1 shows the complications of ET and their incidence reported in studies conducted in the 2000s, although these are all studies on ET for neonatal hyperbilirubinemia [ 34 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The most common complications related to ET procedures are thrombocytopenia and hypocalcemia [ 38 , 49 ].…”
Section: Adverse Effects Of Exchange Transfusionmentioning
confidence: 99%
“…However, ET can lead to more severe complications, such as life-threatening bleeding, sepsis, cardiac dysfunction, necrotizing enterocolitis, and even death, apart from transient hypocalcemia, hyperkalemia, bradycardia, and thrombocytopenia. The mortality rate attributable to the ET procedure has been reported to be 0–8% in several previous studies [ 34 , 38 , 39 , 43 , 48 , 50 ].…”
Section: Adverse Effects Of Exchange Transfusionmentioning
confidence: 99%